The Internalization of Character Education Values in the Halal Bihalal Tradition after Eid al-Fitr - Dimas Fauzi; Abdul Rosyad (The Future of Education Journal, 2026)
The halal bihalal tradition after Eid al-Fitr is a socio-religious practice that has developed within Indonesian Muslim society and embodies various character education values. This tradition functions not only as a means of strengthening social ties (silaturahmi), but also as a medium for internalizing religious, social, and moral values in community life. This study aims to describe the character education values contained in the halal bihalal tradition and the process of their internalization in social life. The study employed a library research approach by examining various written sources relevant to halal bihalal, character education, and Islamic culture. Data collection was conducted through documentation techniques by reviewing literature related to the focus of the study. The data were analyzed qualitatively using content analysis techniques to identify, classify, and interpret character education values within the halal bihalal tradition. The findings reveal that the halal bihalal tradition contains values of religiosity, tolerance, empathy, togetherness, social responsibility, and mutual respect. These values are internalized through habituation, role modeling, and social interactions occurring during halal bihalal activities. In addition, this tradition also plays a role in strengthening social piety and fostering harmonious relationships among individuals and community groups. Halal bihalal serves as an effective culture-based character education medium because it is carried out contextually and involves all levels of society. Therefore, the halal bihalal tradition after Eid al-Fitr has an important contribution to the formation of religious, tolerant, and socially harmonious character in community life.